Defining the Learning Curve for Hip Arthroscopy: A Threshold Analysis of the Volume-Outcomes Relationship. Issue 6 (May 2018) - Mehta, Nabil; Chamberlin, Peter; Marx, Robert G.; Hidaka, Chisa; Ge, Yile; Nawabi, Danyal H.; Lyman, Stephen
Background: Hip arthroscopy has emerged as a successful option for the treatment of femoroacetabular impingement and related hip disorders, but the procedure is technically challenging. Purpose: To define the learning curve through which surgeons become proficient at hip arthroscopy. Study Design: Cohort study; level of evidence, 3. Methods: The authors identified hip arthroscopy procedures performed by surgeons through a New York State database (Statewide Planning and Research Cooperative System) and followed those cases for additional hip surgery (total hip arthroplasty, hip resurfacing, or ipsilateral hip arthroscopy) within 5 years of the original procedure. Career volume for each case was calculated as the number of hip arthroscopy procedures that the surgeon had performed. Volume strata were identified via the stratum-specific likelihood ratio method. A Cox proportional hazards model was used to measure the effect of surgeon career volume on risk of additional hip surgery, adjusting for the following patient characteristics: age, sex, race/ethnicity, insurance type, and concurrent diagnosis of hip osteoarthritis. Results: Among 8041 hip arthroscopies performed by 251 surgeons, 989 (12.3%) cases underwent additional hip surgery within 5 years. Four strata of surgeon career volume associated with distinct frequencies of reoperation were identified: cases in the lowest stratum (0-97) had the highest frequency of additional surgery (15.4%). Frequencies declined for cases in the medium (98-388), high (389-518), and highest (≥519) strata (13.8%, 10.1%, and 2.6%, respectively). There was an increased risk of subsequent surgery in each stratum when compared with the highest stratum (hazard ratio [95% CI]: low volume, 3.22 [2.29-4.54]; medium, 3.40 [2.41-4.82]; high, 2.81 [1.86-4.25]; P < .0001 for all). Patients with a diagnosis of hip osteoarthritis had increased risk of subsequent hip arthroplasty or resurfacing (2.46 [2.09-2.89], P < .0001) . Risk also increased with age: 30 to 39 vs ≤29 years (5.12 [3.29-8.00], P < .0001), 40 to 49 vs ≤29 years (11.30 [7.43-17.190], P < .0001), ≥50 vs ≤29 years (18.39 [12.10-27.96], P < .0001). Increased age and osteoarthritis were not risk factors for revision hip arthroscopy. Conclusion: The learning curve for hip arthroscopy was unexpectedly demanding. Cases performed by surgeons with career volumes ≥519 had significantly lower risk of subsequent hip surgery than those performed by lower-volume surgeons.